2006
DOI: 10.1176/ps.2006.57.6.879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serious Mental Illness and Substance Abuse on Criminal Offenses

Abstract: Unless factors unique to serious mental illness can be specifically associated with behavior leading to incarceration, the criminalization hypothesis should be reconsidered in favor of more powerful risk factors for crime that are widespread in social settings of persons with serious mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(62 citation statements)
references
References 9 publications
5
53
0
Order By: Relevance
“…Similarly, a specialized probation approach for justice-involved individuals with mental illness was superior to general probation in terms of decreased recidivism; however, the improvement was unrelated to symptom amelioration (Skeem et al 2009). Such observations make sense in light of other studies demonstrating that symptoms of serious mental illness are related to criminal behavior in fewer than 10% of offenses (Jurginger et al 2006;Peterson et al 2010).…”
Section: Criminalization: Not Whether Rather Whysupporting
confidence: 55%
“…Similarly, a specialized probation approach for justice-involved individuals with mental illness was superior to general probation in terms of decreased recidivism; however, the improvement was unrelated to symptom amelioration (Skeem et al 2009). Such observations make sense in light of other studies demonstrating that symptoms of serious mental illness are related to criminal behavior in fewer than 10% of offenses (Jurginger et al 2006;Peterson et al 2010).…”
Section: Criminalization: Not Whether Rather Whysupporting
confidence: 55%
“…Some previous research has found that higher levels of perceived coercion lead to better treatment retention over time (35). Mandatory treatment has been found to lead to significant reductions in recidivism, compared with treatment that is not mandatory (22,36). Use of treatment increased for both groups over time.…”
Section: Discussionmentioning
confidence: 84%
“…Some studies have found that outcomes for persons under legal pressure are better than outcomes for those not under legal pressure (21). For example, Junginger and colleagues (22) found that offenders with severe mental illness under involuntary outpatient commitment had fewer arrests than offenders not under mandatory treatment and that the association between mandatory treatment and reduced arrest was mediated by an increase in mental health treatment. Further, Levenson and Macgowan (23) found that participants with higher levels of engagement (for example, attendance) were more likely to progress in group therapy and that prisoners with higher treatment motivation were more likely to receive aftercare treatment, which, in turn, significantly reduced recidivism (24).…”
mentioning
confidence: 99%
“…These include deinstitutionalization and restrictive commitment criteria, which have been said to culminate in the 'criminalization of the mentally ill' (Abramson, 1972). More recently, however, relatively high levels of violence (Wallace et al, 2004) and substance abuse (Junginger et al, 2006) among people experiencing mental illness have been claimed to account for these encounters. Further research should establish whether these specific types of suspect/offender encounters are increasing and if and how these encounters are resolved.…”
Section: Frequency Of Contactsmentioning
confidence: 99%